PELATIHAN KEPEMANDUAN EKOWISATA DALAM PENGEMBANGAN DESA WISATA - Putu Agus Prayogi; Yogantara, Komang Krishna; Sari, Ni Luh Komang Julyanti Paramita; Wartana, Made Hedy (Universitas Triatma Mulya, 2024)
Ecotourism guidance training is a very important activity to be carried out for tour guides. This activity not only trains guides to be able to guide tourists well, but it is hoped that tour guides will be able to direct tourists to understand the principles of sustainable nature conservation. Ecotourism is a tourism concept that focuses on environmental preservation and empowerment of local communities. Ecotourism activities basically have the principles of tourism activities that can foster environmental and cultural awareness, minimize the negative impact of tourism, provide positive experiences to tourists and empower local communities. This ecotourism guidance training activity was carried out in East Duda Village, Karangasem Regency. This activity was attended by the youth organization of East Duda Village, which in the future will be prepared as tour guides. East Duda Village is a tourist village that has natural potential such as Putung Hill, Jagra Satru Waterfall and Beji Dedari. This training was carried out in the context of the KKNT of Triatma Mulya University in 2024. The development of ecotourism has various benefits that include environmental, economic, social, and cultural aspects. Ecotourism promotes the protection of ecosystems and biodiversity. Ecotourism activities will encourage tourists and local communities to become more aware of the importance of protecting the environment. This is due to ecotourism management using a sustainable management approach. Resource management is carried out with an environmentally friendly approach to reduce negative impacts such as pollution and deforestation. The development of ecotourism will also help preserve local culture, such as customs, traditional dances, and typical culinary, by making it a tourist attraction. The tourism activities offered in the development of ecotourism encourage tourists to learn to appreciate local culture, and this encourages the community to maintain their cultural heritage